Corn tolerance to florpyrauxifen-benzyl rates and its mixture with atrazine and mesotrione - Godar, Amar S.; Norsworthy, Jason K.; Barber, L. Tom (Frontiers in Agronomy, 2025)
Florpyrauxifen-benzyl is a new synthetic auxin herbicide labeled in rice with a broad spectrum of control, typically more potent on broadleaf weeds. It has garnered some interest as a potential broadleaf weed control option for use in corn at low rates. Field experiments were conducted in Fayetteville, Arkansas, from 2019 through 2021 to examine the response of corn to postemergence applications of florpyrauxifen-benzyl at three rates (7.5, 15, and 30 g ae ha-1), as well as mixtures of the herbicide with atrazine (at half or full rate), mesotrione, or a combination of atrazine (at half rate) and mesotrione. Injury and yield response varied among years, possibly attributed to temperature and solar radiation variations following treatment application. Three weeks after application (WAA), stand-alone florpyrauxifen-benzyl or mixtures caused incrementally greater injury with increasing rates (5% to 76% injury). The levels of early injury were largely sustained at 7 WAA, with a few instances of recovery, particularly with a mixture of florpyrauxifen-benzyl at 7.5 g ae ha-1 with the full rate of atrazine. Corn yield loss generally surpassed the respective injury levels. The yield loss was overall the least in 2020 (8 to 46%) and most severe in 2021 (26 to 93%), largely depending on florpyrauxifen-benzyl rates. Averaged across years, the full rate of atrazine mixed with florpyrauxifen-benzyl at 7.5 g ae ha-1 caused less yield loss (12%) compared to the stand-alone application (28% yield loss). These results suggest that using florpyrauxifen-benzyl in corn, even at low rates and/or in a mixture with atrazine/mesotrione, can cause immediate and sustained injury, often leading to greater than 10% yield reduction. Further research could explore in-crop, in-chemistry, or in-application technology opportunities for mitigating this inadequate safety to render this novel tool a viable option for use in corn.